Wild sun bears (Helarctos malayanus) exhibit aseasonality in parturition - Zachary A. David; Brian Crudge; Matt Hunt; Kirsty Officer; Vuthy Choun; Barbara Durrant; Megan A. Owen; Morokot Long; John P. Whiteman (Theriogenology Wild)
Seasonal reproduction can provide species with fitness advantages by allowing the birth of young to coincide with favorable environmental conditions, particularly in environments with high seasonal and intra-annual variation in these conditions. Seven of the eight species in the bear family (Ursidae) reproduce seasonally in both managed care and the wild; however, data for the eighth species, the sun bear (Helarctos malayanus), is unclear. Sun bears have been observed to reproduce throughout the year in managed care, yet currently there are no clear data of birth timing for wild sun bear cubs. Here we investigate the seasonality of parturition of wild sun bears by utilizing a dataset of body mass measurements from bears placed in the care of the wildlife conservation organization Free the Bears in Cambodia after interception by authorities for illegal removal from the wild. We selected body mass records for all rescued bears ≤5 kg, and modeled growth rates with linear regressions for cubs with >3 measurements. Assuming a mass of 300 g at birth, these growth rates were used to estimate the birth date for each cub. Our results suggest that wild sun bears reproduce aseasonally in Cambodia, with estimated birth dates occurring in all 12 months of the year, and in all 4 of Cambodia’s distinct seasons.